2017
DOI: 10.1371/journal.pone.0188317
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB pathways are involved in M1 polarization of RAW 264.7 macrophage by polyporus polysaccharide in the tumor microenvironment

Abstract: Bladder cancer is one of the most malignant tumors closely associated with macrophages. Polyporus polysaccharide (PPS) has shown excellent efficacy in treating bladder cancer with minimal side effects. However, the molecular mechanisms underlying the effects of PPS in inhibiting bladder cancer remain unclear. In this study, we used macrophages cultured alone or with T24 human bladder cancer cell culture supernatant as study models. We found that PPS enhanced the activities of IFN-γ-stimulated RAW 264.7 macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 33 publications
2
74
0
Order By: Relevance
“…M1 macrophage differentiation is involved with the coactivation of the NF‐κB and STAT3 pathways in miR‐15a/16 −/− mice in tumour or inflammation. Polyporus polysaccharide activates the NF‐κB signalling pathway by interfering with IκB phosphorylation for M1 macrophage polarization . P21 regulates macrophage reprogramming by shifting the balance between active p65‐p50 and inhibitory p50‐p50 NF‐κB pathways .…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophage differentiation is involved with the coactivation of the NF‐κB and STAT3 pathways in miR‐15a/16 −/− mice in tumour or inflammation. Polyporus polysaccharide activates the NF‐κB signalling pathway by interfering with IκB phosphorylation for M1 macrophage polarization . P21 regulates macrophage reprogramming by shifting the balance between active p65‐p50 and inhibitory p50‐p50 NF‐κB pathways .…”
Section: Discussionmentioning
confidence: 99%
“…SHH treatment upregulated the expression of iNOS and TNF-α mRNA ( Figure 2B). Activation of the NF-κB signaling pathway has been reported to induce M1 macrophage differentiation and the consequent inflammatory effects [14,21]. To establish if NF-κB activation is involved in the SHH-induced upregulation of iNOS and TNF-α mRNA expression, the NF-κB inhibitor BAY11-7085 was combined with SHH treatment.…”
Section: Reduction Of Il-4-induced M2 Polarization In Mouse Peritoneamentioning
confidence: 99%
“…Previous studies found that polyporus polysaccharide (PPS) could alleviate the adverse reactions of Bacille Calmette-Guerin BCG and improve its e ciency [12], and effectively inhibit the progression of N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN)-induced bladder cancer in rats [13]. In the following study, PPS was found to increase the expression level of CD86 and CD40 in bladder cancer tissue of rats [12], and regulate the immune activity of macrophages and promoted them to M1-like macrophages [14]. Therefore, it was speculated that PPS inhibited the progression of bladder cancer by regulating macrophage polarization in tumor macroenvironment.…”
Section: Introductionmentioning
confidence: 77%